Avaliação da participação de citocinas (interleucina 32, interleucina 10, fator de necrose tumoral) e receptores similares a Toll (TLR 4) na infecção por Leishmania (Viannia) sp. - Galdino Júnior, Hélio (2013)
American Tegumentary Leishmaniasis (ATL) is a disease caused by protozoa Leishmania. In Brazil, the most prevalent species is L. (Viannia) braziliensis. Several cytokines and receptors are involved in immunopathogenesis of ATL, however, the role of interleukin 32 (IL-32) was not investigated in this disease. Besides, toll-like receptors (TLR) were poorly evaluated in Leishmania infection, especially when it is caused by L. (V.) braziliensis. The aim of the present study was to evaluate IL-32, TNF and IL-10 expression in ATL lesions; the induction of IL-32 by L. (V.) braziliensis amastigotes in human peripheral blood mononuclear cells (PBMC) cultures as well as the involvement of TLR4 in monocyte/macrophage response to L. (V.) brazilienis amastigotes. Biopsies fragments from cutaneous and mucosal lesion and healthy tissues were used to investigate the subgenus of the parasites by PCR-RFLP assay; expression of IL-32, TNF and IL-10 was assayed by immunohistochemistry and expression of IL-32 isoforms     , TNF and IL-10 was analysed by qRT-PCR. The PBMC were cultured with L. (V.) braziliensis amastigotes in the absence or presence of IFN and IL-32 induction was assayed by qRT-PCR; and TNF and IL-10, by ELISA. TLR4 was neutralized by monoclonal antibodies and lipopolysaccharide (LPS) was used as TLR4 agonist. The expression of TLR4 in monocyte/macrophages was evaluated by flow cytometry. Thirty five patients were evaluated, 23 with cutaneous leishmaniasis (CL) and 12 with mucosal leihsmaniasis (ML). All parasite positive samples contained L. (Viannia) sp. The expression of IL-32 (protein and mRNA) was similar in CL and ML lesions but was higher than in health tissues. Only IL-32 was detected. The proteins TNF and IL-10 were detected in similar levels in CL and ML lesions, but TNF mRNA was present in higher levels in ML (4.069x) than in CL lesions (141 x, p < 0.05). L. (V.) braziliensis amastigotes induced IL-32, TNF and IL-10 in IFN pre-treated PBMC. The production of TNF and IL-10 was TLR4 dependent and treatment of PBMC with LPS further increased the production of TNF induced by amastigotes (p < 0.05). However, LPS did not altere the IL-10 production. Treatment with IFN enhanced the percentage of TLR4+ monocyte/macrophage (p < 0.05), which was decreased following incubation with amastigotes (p = 0.06). The results showed that IL-32 is produced during L. (Viannia) infection and TLR4 mediates L. (V.) braziliensis amastigote-induced TNF and IL-10 production in human PBMC. Moreover, the data suggest that amastigotes can lead to TLR4 internalization what can allow parasite to evade of innate immune response. This study indicates that IL-32 and TLR4 are important players in human infection caused by L. (Viannia), especially L. (V.) braziliensis. Whether TLR4 is also important to IL-32 production by human monocytes/macrophages deserves further investigation.